Papular Acantholytic Dyskeratosis of the Vulva: A Case Report and Literature Review - Sakpuwadol N; Suchonwanit P (Clinical, Cosmetic and Investigational Dermatology)
Nawara Sakpuwadol, Poonkiat Suchonwanit Division of Dermatology, Department of Medicine, Faculty of Medicine, Ramathibodi Hospital, Mahidol University, Bangkok, ThailandCorrespondence: Poonkiat Suchonwanit, Division of Dermatology, Department of Medicine, Faculty of Medicine, Ramathibodi Hospital, Mahidol University, 270 Rama VI Road, Ratchathewi, Bangkok, 10400, Thailand, Tel +66-2-2011141, Fax +66-2-201-1211 Ext 4, Email poonkiat@hotmail.comAbstract: Papular acantholytic dyskeratosis (PAD) of the vulva is an uncommon benign condition characterized by multiple hyperkeratotic papules in the anogenital region. First described in 1984, PAD belongs to the spectrum of focal acantholytic dyskeratoses and shares histopathological features with Darier disease and Hailey-Hailey disease. Despite its persistence, PAD is benign, requiring only reassurance in many cases. However, various treatment modalities have been reported for symptomatic patients, including topical and systemic therapies, and procedural interventions. We present a case of a 21-year-old Thai woman with asymptomatic perivulvar papules with typical histopathological features of PAD. After conservative management, the patient remained asymptomatic during follow-up. Additionally, we present a review of the current literature on this uncommon entity. This case highlights the importance of clinicopathological correlation in diagnosing PAD and distinguishing it from other clinically similar disorders. We discuss the clinical presentation, histopathological features, differential diagnosis, potential genetic associations, and management options for PAD.Keywords: benign tumor, Darier disease, focal acantholytic dyskeratosis, genetic, genital papule, Hailey-Hailey disease